The validity of critical speed determined from track cycling for identification of the maximal lactate steady state - de Lucas, R. D. (2002)
The objective of this study was to determine the critical speed (CS) for track cycling and to assess whether a lactate steady state occurs at this speed. Fourteen competitive cyclists performed the following tests on an official cycling track (333.3 m): 1) incremental test for determination of the intensity corresponding to 4 mM of blood lactate (onset of blood lactate accumulation, OBLA) and maximal oxygen uptake (VO(2)max); 2) CS: 3 maximal bouts for distances of 2, 4 and 6 km executed in random order and with a period of recovery of 40 to 50 min between bouts. CS was determined for each subject from the linear regression between the distance and the time taking to cycle it; 3) Endurance test in which subjects were instructed to pedal at 100% of their individually determined CS for 30 min. At the 10(th) and 30(th) min (or upon exhaustion), 25 mul of blood were collected from ear lobe for later analysis of blood lactate [Lac]b. An increase less than or equal to1 mM between 10 and 30 min of exercise was considered as the criterion for the occurrence of the lactate steady state. CS (49.6 +/- 8.6 ml.kg(-1).min(-1); 36.9 +/- 2.7 km.h(-1)) was significantly higher than OBLA (43.7 8.0 ml.kg(-1).min(-1); 35.24 +/- 2.6 km.h(-1)) although the two parameters were highly correlated (r=0.97). During the endurance test, only 8 of the 14 subjects completed the 30 min period at CS. of these 8 subjects, only 2 presented a lactate steady state. Time to exhaustion at CS was 20.3 +/- 1.6 min for the remaining 6 subjects. The 12 subjects who did not reach a lactate steady state presented mean [Lac]b values of 7.4 +/- 1.3 mM at 10 min and of 9.4 +/- 1.9 mM at the end of the test (exhaustion), characterizing an exercise intensity of high lactacidemia. on the basis of the present results, we can conclude that CS determined by a track cycling test seems to overestimate the intensity of the maximal lactate steady state for most subjects.